STRATEGI PENGEMBANGAN EKOWISATA DI DESA APAR BERBASIS KOMUNITAS : PENDEKATAN ANALISIS SWOT [COMMUNITY-BASED ECOTOURISM DEVELOPMENT STRATEGY IN APAR VILLAGE: SWOT ANALYSIS APPROACH] - Nanda, Rama; Marhamah, Ithvi; Notrilauvia, Nindy (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to formulate a sustainable, community-based ecotourism development strategy for Desa Apar in Pariaman City. The village has significant ecotourism potential through its mangrove ecosystem, local traditions, and community engagement. A descriptive qualitative approach was applied using SWOT analysis to assess internal and external factors affecting tourism development. Data collection involved field observation, semi-structured interviews with stakeholders, and documentation review. Findings show that Desa Apar holds a strong internal position (score: 4.36) and favorable external opportunities (score: 4.40), placing it in Quadrant I of the SWOT matrix. This indicates that aggressive strategies can be implemented by leveraging existing strengths to capture available opportunities. Recommended strategies include infrastructure improvement, community training, conservation-based educational tourism, sustainable waste management, and diversification of mangrove-based products. These approaches aim to strengthen local welfare while preserving environmental sustainability. This research contributes to the field by offering an integrated SWOT-based framework for rural ecotourism planning that balances ecological protection and economic development.